Gasification of raw and torrefied empty fruit bunch using bubbling fluidized bed - N. H., Abdul Halim; Suriyati, Saleh; Noor Asma Fazli, Abdul Samad (IOP Publishing Ltd, 2020)
An experimental study of bubbling fluidized bed gasification process using empty fruit bunch (EFB) as a feedstock has been performed in order to study the effect of gasification temperature on gasification performance. Two types of EFB have been used, which are raw EFB and torrefied EFB at 300 °C. The composition of the synthesis gas, gas yield, low heating value (LHV), cold gas efficiency (CGE), and carbon conversion (CC) was determined and analyzed. In terms of synthesis gas, the composition of hydrogen and carbon monoxide gases were increased while methane and carbon monoxide gases were decreased for raw and torrefied EFB when the temperature is increased from 650 to 900 °C. Meanwhile, the synthesis gas yield was significantly enhanced and reached the maximum value of 1.21 and 1.45 MJ/Nm3 for raw and torrefied EFB respectively, which indicates that the torrefaction process improves the synthesis gas yield. Besides, the LHV for the torrefied EFB at highest gasification temperature is 11.08 MJ/Nm3 which is higher than raw EFB (10.81 MJ/Nm3 ). However, the value of CGE and CC of torrefied EFB are lower than raw EFB with the different about 3% and 5% respectively.